Jewish Liberal Politics in Tsarist Russia, 1900-14 - Gassenschmidt, Christoph. author. aut Link
XVIII, 244 p.
Keywords: Contrary general perceptions concerning Russia during this era, Jewish political activities continued beyond 1907, and given the political limits of Tsarist Russia, transformed and modernized Jewish society to the fullest extent possible. From 1900 to 1914 Jewish Liberals initiated, organised and coordinated various forms of Jewish representation in Russian politics in order to achieve legal emancipation, national- cultural autonomy and even more important the integration of Russian Jews into a modernizing Russian society and economy.